Tilapia skin peptides, a by-product of fish processing, ameliorate DSS-induced colitis by regulating inflammation and inhibiting apoptosis - Gao, Jiahui; Li, Lixiang; Zhao, Dong; Wang, Xia; Xia, Yanan; Li, Bing; Liu, Chang; Zuo, Xiuli (Frontiers in Nutrition, 2022)
Intestinal bowel disease (IBD) has always been tough to treat, therefore researchers are struggle to look for treatments that are safe, low cost, and effective. Food-derived peptides are thought to have anti-inflammatory and antioxidant properties, but they have not been studied in depth in the treatment of IBD. Based on this, we explored the effect of tilapia skin peptides (TSPs) on the remission of colitis in the present study. Colonic epithelial cell lines CT-26 and HT-29 were co-treated with lipopolysaccharide (LPS) and TSPs for 12h. Cell viability was assessed by CCK8 assay. DSS-induced colitis model was established and 100 mg/kg TSPs were oral administered at the same time as DSS intervention. Colonic mucosal barrier function was assessed by western blotting. The inflammatory responses were evaluated by quantitative real-time PCR along with ELISA, respectively. Apoptosis was investigated by TUNEL and flow cytometry. LC-MS/MS was used to characterize peptides composition of TSPs. It was found that TSPs significantly inhibit LPS-induced inflammation and apoptosis in vitro without affecting cell viability. Moreover, the upregulation and activation of Caspase-3 and Caspase-8 were also reversed by TSPs. Subsequently, in vivo experiments demonstrated that TSPs can attenuate DSS induced colitis, manifested by a decrease in weight loss and colon shortening. The expression of ZO-1 and occluding were significantly increased, and the pro-inflammatory cytokines were down-regulated. Meanwhile, TSPs alleviated DSS-induced apoptosis and reduced the expressions of Caspase-3 and Caspase-8. Finally, we found that TSPs were composed of 51 short peptides, and 12 of them were predicted to have significant biological activity. Collectively, this study suggested that TSPs can alleviate colon damage caused by foreign stimuli via inhibiting inflammation and apoptosis which indicated that it has great potential value for the treatment of IBD.